Responsiveness and minimal clinically important difference for pain and disability instruments in low back pain patients - Korsholm Lars; Manniche Claus; Hartvigsen Jan; Lauridsen Henrik H; Grunnet-Nilsson Niels (BMC Musculoskeletal Disorders, 2006)
Abstract Background The choice of an evaluative instrument has been hampered by the lack of head-to-head comparisons of responsiveness and the minimal clinically important difference (MCID) in subpopulations of low back pain (LBP). The objective of this study was to concurrently compare responsiveness and MCID for commonly used pain scales and functional instruments in four subpopulations of LBP patients. Methods The Danish versions of the Oswestry Disability Index (ODI), the 23-item Roland Morris Disability Questionnaire (RMQ), the physical function and bodily pain subscales of the SF36, the Low Back Pain Rating Scale (LBPRS) and a numerical rating scale for pain (0–10) were completed by 191 patients from the primary and secondary sectors of the Danish health care system. Clinical change was estimated using a 7-point transition question and a numeric rating scale for importance. Responsiveness was operationalised using standardardised response mean (SRM), area under the receiver operating characteristic curve (ROC), and cut-point analysis. Subpopulation analyses were carried out on primary and secondary sector patients with LBP only or leg pain +/- LBP. Results RMQ was the most responsive instrument in primary and secondary sector patients with LBP only (SRM = 0.5–1.4; ROC = 0.75–0.94) whereas ODI and RMQ showed almost similar responsiveness in primary and secondary sector patients with leg pain (ODI: SRM = 0.4–0.9; ROC = 0.76–0.89; RMQ: SRM = 0.3–0.9; ROC = 0.72–0.88). In improved patients, the RMQ was more responsive in primary and secondary sector patients and LBP only patients (SRM = 1.3–1.7) while the RMQ and ODI were equally responsive in leg pain patients (SRM = 1.3 and 1.2 respectively). All pain measures demonstrated almost equal responsiveness. The MCID increased with increasing baseline score in primary sector and LBP only patients but was only marginally affected by patient entry point and pain location. The MCID of the percentage change score remained constant for the ODI (51%) and RMQ (38%) specifically and differed in the subpopulations. Conclusion RMQ is suitable for measuring change in LBP only patients and both ODI and RMQ are suitable for leg pain patients irrespectively of patient entry point. The MCID is baseline score dependent but only in certain subpopulations. Relative change measured using the ODI and RMQ was not affected by baseline score when patients quantified an important improvement.